A computational framework for quantifying reactivity of fly ash in cement pastes from backscattered electron images. (10th March 2019) - Park, S.M.; Yang, Beomjoo; Jeon, Haemin
Abstract: A computational framework for quantifying reactivity of fly ash in cement pastes from backscattered electron images is proposed. Alkali-activated fly ash samples were synthesized, and were used for acquiring backscattered electron images at various ages. The obtained images were processed by a computational tool, which employs image binarization using adaptive threshold, and region-of-interest-based objective contour. The proposed scheme offered means of quantifying various information from images such as volume of cracks/voids, unreacted particles, and binder matrix. The degree of reaction of fly ash in alkali-activated fly ash samples at various ages was calculated and compared with that obtained by selective dissolution experiments. The result shows that the proposed computational scheme can be used for quantifying the reactivity of fly ash in cement pastes.